A GVNS Algorithm for Solving the Multi-Depot Vehicle Routing Problem - Bezerra, Sinaide Nunes; de Souza, Sérgio Ricardo; Souza, Marcone Jamilson Freitas (Electronic notes in discrete mathematics, 2018)
This paper presents an algorithm based on the General Variable Neighborhood Search (GVNS) metaheuristic for solving the Multi-Depot Vehicle Routing Problem (MDVRP). The MDVRP consists in designing a set of vehicle routes serving all customers, such that the maximum number of vehicle per depot and vehicle-capacity are respected, and the total cost of transportation is minimized. The proposed algorithm uses Randomized Variable Neighborhood Descent (RVND) as local search method and it is tested in classical instances of the problem. The obtained results are presented and discussed in this paper.